Sociocultural intelligence : a new discipline in intelligence studies - Patton, Kerry (Continuum intelligence studies., 2010)
The book offers an in-depth analysis and conceptualization of a much needed intelligence discipline, Sociocultural intelligence (SOCINT). SOCINT means observing and analyzing such elements as the land, the people, and their communities. Customs, moral attitudes, and culture of foreign populations are integrated into the analysis of the information gathered to maximize the efficiency of security initiatives. A key tool in intelligence and covert operations, SOCINT can mostly be used for non-lethal operations that require a thorough understanding of networks and systems. Simply, by understanding.